Factors influencing success rate of ceramic veneers on endodontically treated anterior teeth: A systematic review - Lin, J.; Bennani, V.; Aarts, J.M.; Brunton, Paul; Ratnayake, J. (2023)
Statement of problem: More conservative restorative approaches have been advocated for nonvital anterior teeth as an alternative to complete coverage crowns to maximize the preservation of tooth structure. Systematic reviews that investigated factors influencing the success rate of porcelain veneers on endodontically treated anterior teeth are lacking. Purpose: The purpose of this systematic review was to investigate factors influencing the success rate of porcelain veneers on endodontically treated anterior teeth. Material and methods: Searches were performed across Medline/PubMed, Google Scholar, Scopus, and Web of Science electronic databases. In addition, articles were hand searched from references of systematic reviews concerning porcelain veneers and endodontically treated teeth. Results: After screening and applying the eligibility, inclusion, and exclusion criteria, 7 articles met the inclusion criteria. Factors that could positively influence the success rate of endodontically treated anterior veneered teeth were immediate dentin sealing, labially positioning of the endodontic access cavity, and incorporating fiber posts. Conclusions: The use of fiber posts and labial positioning of the endodontic access cavity could positively influence the success rate of porcelain veneers on endodontically treated teeth. The effect of immediate dentin sealing on the survival rate of endodontically treated veneered teeth is still unclear and further research is needed.